(untitled) (Journal of Geography and Environmental Management, 2019)
Climate is one of the elements of assessment of the recreational potential of lakes and natural objects. Generally influence of climate is manifested through human reaction to the weather, in particular, light, day length, total solar and ultraviolet radiation, air transparency, temperature and humidity, wind speed, cloudiness and etc. These indicators determine the degree of favorability for various types of recreation. The article provides climatic assessment of lakes for eco-tourism, excursions and beach tourism. The territory of Kazakhstan was zoning in accordance of duration of a comfortable period for three tourism types. Caused by lack of data about the water temperature for reviewed lakes (Markakol, Zhaisan, Inder, Kolsay lakes, the Caspian Sea, Shaitankol, etc.) we used intervals of comfortable air temperatures, according to which the water surface should be sufficiently heated for the beach tourism activities. For individual lakes in Kazakhstan with high recreational value as example of different latitudinal and highaltitude zones for each type of tourism was done detailed analysis of comfort temperatures during the warm period (April-October). For each type of recreational activity were compiled maps of the duration of a comfortable period on the territory of Kazakhstan, what makes it possible to identify promising types of tourism near objects of touristic interest.